2019
DOI: 10.1186/s12936-019-2832-9
|View full text |Cite
|
Sign up to set email alerts
|

Setting the scene and generating evidence for malaria elimination in Southern Mozambique

Abstract: Mozambique has historically been one of the countries with the highest malaria burden in the world. Starting in the 1960s, malaria control efforts were intensified in the southern region of the country, especially in Maputo city and Maputo province, to aid regional initiatives aimed to eliminate malaria in South Africa and eSwatini. Despite significant reductions in malaria prevalence, elimination was never achieved. Following the World Health Organization’s renewed vision of a malaria-free-world, and consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 24 publications
0
61
0
1
Order By: Relevance
“…This study is reported as per the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines (S1 Checklist). The project was conducted jointly with the Ministry of Health (MoH) and district health authorities, building on the programmatic activities planned for the district [9]. Fig 1 shows the implementation timeline of interventions and the data collection methods.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is reported as per the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines (S1 Checklist). The project was conducted jointly with the Ministry of Health (MoH) and district health authorities, building on the programmatic activities planned for the district [9]. Fig 1 shows the implementation timeline of interventions and the data collection methods.…”
Section: Methodsmentioning
confidence: 99%
“…The GTS further recommends that surveillance should be used as an intervention through the implementation of response strategies to malaria cases when transmission is low [7,8]. In this context, the Magude project was designed to evaluate the feasibility of malaria elimination in sub-Saharan Africa using a comprehensive mix of interventions recommended by the GTS [9], including a strengthened surveillance system, case management, vector control with LLINs and IRS, and mass drug administration (MDA). This article presents the impact evaluation of the project on P. falciparum malaria cases, and the changes observed in prevalence, incidence, and inpatient admissions and mortality in Magude district, southern Mozambique.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this objective, drug research should direct on validated novel targets to isolate a new lead compound. 39,41 The need for identifying novel metabolic targets comes from several reasons. Firstly, except atovaquone and artemisinin derived drugs, most antimalarial agents have no chemical diversity, which may lead to cross-resistance.…”
Section: Novel Antimalarial Targetsmentioning
confidence: 99%
“…Identification of novel drug targets and the design of new compounds acting on new targets is nowadays widely used approach all over the world to combat issues raised by the emergence of resistance to existing drugs. 40,41 Therefore, investigating inhibitors specific to the new target proteins of the malaria parasite has been exploited for drug target identification. Since the unveiling of the P. falciparum genome, several novel targets for drug intervention have emerged.…”
Section: Novel Antimalarial Targetsmentioning
confidence: 99%
“…Following the GTS recommendations [14], the project combined an optimized package of existing interventions, including a strengthened surveillance system, case management, intensified vector control with universal long-lasting insecticide treated net (LLIN) distribution and universal (i.e. targeted to all households in the district) indoor residual spraying (IRS), and mass drug administration (MDA) [21]. The project was based on direct implementation of malaria interventions and was managed on a learning-by-doing basis, with resources for MDA delivery adjusted over time based on experience accumulation.…”
Section: Introductionmentioning
confidence: 99%